Brexit: a requiem for the post-national society?. Issue 1 (29th January 2019) - Favell, Adrian
Abstract : The 'fourth freedom' of freedom of movement of persons – somewhat misleadingly labelled 'European citizenship' – lay at the normative heart of the European project. Although sceptics have often suggested it was part of the building of a European fortress, or even a last gasp of elite European colonial privilege, the essential point of EU freedom of movement was its revolutionary introduction of a regionally expansive non-discrimination by nationality, going well beyond established abstract notions of 'personhood' and human rights on which other global egalitarian movements depend. For sure, it had been battered by roll back in national courts, suspension of Schengen, and new external borderings, well before the Brexit vote. Yet the practice of the fourth freedom in terms of everyday transactions and interactions struck at the heart of the core of the modern Hobbesian nation state: its sovereignty to decide on the boundaries of its own, increasingly de-territorialised population, which was also its power to shore up the most potent source of global inequalities – the birthright lottery which protects the 'wealth of nations' and the privileges of democratic 'peoples' from the unbounded effects of de-territorialised mobilities. As we are also seeing – and hearing among many ostensibly progressive academic voices – the putatively egalitarian voice of people's democracy can be used to further bolster the shrinkage of moral community within the nation state. The essay takes upon itself to evaluate what is being lost normatively in terms of the return of the national – methodologically as much as politically – as the slow motion car crash of Brexit happens and after it takes place.